2010
DOI: 10.1097/bsd.0b013e31819e31a4
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Patient Perceived Outcomes in Patients 55 Years and Older Undergoing Anterior Cervical Discectomy and Fusion

Abstract: On the basis of our statistically significant improvement in NDI and SF-36 scores, as a measure of patient perceived outcome after ACDF surgery, outcomes after ACDF surgery in patients over 55 years of age are not significantly different than those of a younger patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There are studies that demonstrate than in a short term follow up posterior decompression has better results compared with an anterior approach, but in a longer follow up no differences were found. 17,20,21 Our study had several limitations. The patients were not randomized to the surgical procedure they underwent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are studies that demonstrate than in a short term follow up posterior decompression has better results compared with an anterior approach, but in a longer follow up no differences were found. 17,20,21 Our study had several limitations. The patients were not randomized to the surgical procedure they underwent.…”
Section: Discussionmentioning
confidence: 95%
“…The follow-up period is short, so we believe that patients with anterior decompression show a clinical improvement at 2 years, as reported in other studies. [19][20][21] …”
Section: Discussionmentioning
confidence: 98%
“…According to Aragones et al, the improvements in NDI and VAS scores are significantly better with arthroplasty than with arthrodesis (29,37) . The results of Li et al showed that although ACDR resulted in a lower rate of adjacent segment degeneration and subsequent corrective surgeries in less than 7 years after the primary surgery, ACDR patients had similar NDI and VAS scores to those of ACDF (31) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that the conventional cervical surgical technique, namely ACDF surgery, causes improvements in NDI and VAS (29) . Some studies examined outcomes of fusion patients (30)(31)(32)(33)(34) , whereas others compared fusion with arthroplasty (15,16,26,28,(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%
“…We elected to look at anterior cervical discectomy and fusion (ACDF) given that it is one of the most common spinal procedures performed, with a well-established surgical approach, high success rate, consistent operative time, and predictable length of hospital stay, as well as high variability in operating room costs. [5][6][7]…”
Section: Introductionmentioning
confidence: 99%